Designing Fe-containing polyhedral oligomeric silsesquioxane to endow superior mechanical and flame-retardant performances of polyamide 1010. (1st March 2023) - Ye, Xinming; Meng, Xiangning; Han, Zhiqing; Qi, Yugang; Li, Zhimao; Tian, Panpan; Wang, Wensheng; Li, Jie; Li, Yingchun; Zhang, Wenchao; Yang, Rongjie
Abstract: With increasing attention to environmental safety and health, long-chain biologically-based polyamides (PA) are considered to be promising materials owing to their biocompatibility and combining the dual advantages of polyolefins and short-chain petroleum-based polyamides. However, poor flame retardancy severely impedes long-chain biologically-based polyamides' application in versatile high-standard fields. Herein, we introduced Fe element into the polyhedral oligomeric silsesquioxane (POSS) cage to obtain iron-containing hepta-phenyl POSS (Fe-Ph-POSS), deriving from the chemical reaction between Li-Ph-POSS and FeCl3 . The chemical structure of Fe-Ph-POSS was fully characterized and confirmed by FTIR, 1 H NMR, 13 C NMR, Solid state 29 Si NMR, XPS and MALDI-TOF MS. Thereafter, Li-Ph-POSS and Fe-Ph-POSS were adopted to flame retarded biologically-based PA1010. The addition of 10 wt% Fe-Ph-POSS distinctly enhanced the thermal stability without affecting the melting and crystallization temperature of PA1010 composites. Additionally, the introduction of Fe-Ph-POSS did not cause embrittlement for PA1010 and almost completely maintained its excellent mechanical properties (elongation at break, tensile and impact strength were reached 473.8%, 46.87 MPa and 4.52 kJ/m 2, respectively). The burning tests results suggested that 10 wt% Fe-Ph-POSS increased the LOI value of PA1010 from 22.6 to 28.4%, and the generation of red-brown char layers rich in iron-containing silicates and carbonates, which effectively hindered the release of heat, smoke and toxic volatiles. Thereby imparting the resultant PA1010 composites to superior flame-retardant performances. Therefore, our work offers an exceptional thought for construction of high-performance biologically-based polyamide composites based on environmentally friendly organic-inorganic hybrid nanomaterials. Graphical abstract: Image 1 Highlights: Fe-containing hepta-phenyl polyhedral oligomeric silsesquioxane is synthesized via one-pot method. The incorporation of Fe-Ph-POSS almost completely maintains its superior mechanical properties. Fe-Ph-POSS apparently mitigates fire hazards of the formed biologically-based PA1010 composites. The flame-retardant mechanism of Fe-Ph-POSS for PA1010 is fully illustrated.